Case report: A novel compound heterozygous variant in the COL4A3 gene was identified in a patient with autosomal recessive Alport syndrome - Chen, Sha; Zhang, Yufeng; He, Jinjin; Yang, Dingwei (Frontiers in Genetics, 2024)
Alport syndrome (AS), a hereditary kidney disease with high risk of renal failure, is attributed to the pathogenic variants in genes COL4A3, COL4A4 or COL4A5 that encode type IV collagen. The next-generation sequencing (NGS) is increasingly applied to the diagnosis of AS, but complex genotype-phenotype correlation, that is identifying the significance of variants, is still a huge clinical challenge. Here, we reported a 27-year-old Chinese woman with a family history of hematuria and proteinuria. Notably, the proband is the only one in her family who showed renal insufficiency. NGS was performed in this family and revealed that the proband was compound heterozygote for two variants in the COL4A3 gene, including c.2990G>A inherited from her father and c.4981C>T inherited from her mother. We modeled the spatial structure of corresponding protein and supposed that structural abnormalities led to the breakdown of type IV collagen networks, a major component of glomerular basement membrane. Thus, the proband was diagnosed with autosomal recessive AS characterized by severe defects of glomerular basement membrane. It is why the proband showed the loss of renal function. This case presentation emphasizes the importance of NGS for AS diagnosis and provides a novel genotype of AS.